PENERAPAN HUKUM DALAM PENYELESAIAN KASUS PIDANA TERHADAP OKNUM PANDITA (KAJIAN PUTUSAN NO 266/Pid.B/2021/PN Dps) - NI LUH ARININGSIH SARI (GANEC SWARA, 2022)
The purpose of this study is to find out how the law is applied to an individual Pandita who is a holy person (purified) according to Hinduism when he is exposed to a criminal case (immoral crime), and to find out what the judges consider in giving their decision as stated contained in Decision Number 266/ Pid.B/2021/PN Dps. In this study used 3 (three) approaches, namely: a. the statutory approach, b. Conceptual approach, c. Philosophical approach. In the application of law to an individual who is involved in a criminal case, there are two legal systems, namely the application of customary law, namely: with the revocation of the defendant's kesulinggihan status so that he returns to being a walaka (a person outside of the sulinggih) so that there is no word "excluded/specialized". Judges in the proceedings at trial carry out positive law, namely by applying the contents of article 289 of the Criminal Code and the proceedings using the Criminal Procedure Code as law The formal form is from the Criminal Code as its Material Law. That the judge's considerations in deciding this immoral case have studied carefully observing evidence and expert witnesses from doctors and from the Bali PHDI as well as conducting a study of the values that live in society, especially the law. Balinese custom a The Panel of Judges stated that the defendant had violated the contents of Article 289 of the Criminal Code and was sentenced to 4 (four) years and 6 months in prison